Destination vs. Origin-based Commodity Taxation in Large Open Economies with Unemployment - Fabio Antoniou; Panos Hatzipanayotou; Nikos Tsakiris (Center for Economic Studies and ifo Institute (CESifo), 2015)
We construct a perfectly competitive general equilibrium model of two large and symmetric countries producing tradable commodities and a public consumption good. Destination or origin-based taxes are levied on the consumption of the tradable goods. In both countries, an institutional minimum wage leads to involuntary unemployment. We derive the Nash equilibrium consumption taxes under the two taxation principles and compare them to their cooperative rates and to their rates when countries are small. We demonstrate that terms of trade effects are absent in destination-based taxation, but they exist under origin-based taxation. Both taxation principles lead to ambiguous employment externalities. Nash equilibrium destination-based taxes are inefficiently low when the exporting sector in each country is non-labor intensive. The Nash equilibrium origin-based taxes can either be higher or lower that the corresponding cooperative rates.
Keywords: F16; H21; H87; 330; Nash vs. cooperative destination and origin based consumption taxes; terms of trade effects; minimum wage and unemployment